Analysis of Students’ Difficulties in Translating Descriptive Text from Indonesian into English - Laras Tri Rizki; Jaya Nur Iman; Desi Surayatik (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2024)
The aims of this research was to find out the students’ difficulties into English and to know how the students were cope with the difficulties in translating descriptive text from Indonesian into English at the eighth grade students of junior high school Tri Dharma Palembang. The descriptive qualitative research was used in this sample of this research. The sample of this research was the eighth grade students at Junior High School Tri Dharma Palembang. There were fifteen participants of students and there was one participant of their English teacher. The data was taken by using test and interview as the instrument. The research finding showed that the highest percentage of students’ difficulties in translating was grammar (27%). the highest number of the students’ grammar difficulties was phrase (45%). The second difficulty faced by students was clarity and cohesion & naturalness (24%). The third difficulty face by students was spelling & style (14%) and the last difficulty was realizing & understanding (11%). Based on the result of students and their English teacher interview matrix, it showed that students asked their friends and teacher to help solving their problem. It could be concluded that students had difficulties in translating Indonesian descriptive text into English was Grammar and the students asked their friends or teacher to give them a help.